Lecture, expérience et apprentissage : apports pédagogiques à partir de L’intuition de l’instant de Gaston Bachelard - Vargas, Carlos Juliao (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
This article examines the relation between reading, experience, and learning, based on the exercise of learning reading that Bachelard performs in his Intuition of the Instant about Gaston Roupnel’s book Siloë, where his ideas about time and duration -- stemming from his academic training and the reading of Bergson’s work -- are confronted. The problematics of learning is addressed, as well as the pedagogy of demonstration and imagination. It is confirmed that one learns against prior knowledge, deconstructing incorrect knowledge, and overcoming mental obstacles. Following Bachelard’s experience, the possibility of a pedagogy centered on the recovery of the precise moment of learning is raised, rethinking everything that an orthodox conception of the didactic task leaves out without taking advantage of the hermeneutical richness of the learning process.